THE RELATIONSHIP BETWEEN LIFESTYLE AND BLOOD GLUCOSE LEVELS IN PATIENTS WITH DIABETES MELLITUS AT WONOKROMO PUBLIC HEALTH CENTER - Wulandari, Maulidia Ajeng; Rusdianingseh; Umamah, Faridah; Putri, Rahmadaniar Aditya (Universitas Nahdlatul Ulama Surabaya, 2025)
Background: Diabetes mellitus is a chronic condition with rising global prevalence and is strongly influenced by lifestyle behaviors. Objective: This study examined the association between lifestyle factors and blood glucose levels among patients with diabetes mellitus at the Wonokromo Public Health Center. Methods: The study included 216 patients with diabetes mellitus, of whom 141 were selected using purposive sampling. A correlational analytic design with a cross-sectional approach was employed. Data were collected using a lifestyle questionnaire and the respondents’ most recent blood glucose measurements. Statistical analysis was conducted using the Spearman rank test. Results: Nearly half of the respondents reported a moderate lifestyle pattern, and most had blood glucose levels within the normal range. The analysis yielded a p-value < 0.001 with a correlation coefficient (r = 0.385), indicating a significant association between lifestyle and blood glucose levels. Conclusion: The findings demonstrate that lifestyle is significantly related to blood glucose control in patients with diabetes mellitus. These results highlight the importance of adopting healthy lifestyle practices, including balanced diet, regular physical activity, stress management, and avoidance of smoking, to help maintain optimal blood glucose levels.